Rationale and design for the detection and neurological impact of cerebrovascular events in non-cardiac surgery patients cohort evaluation (NeuroVISION) study: a prospective international cohort study. Issue 7 (6th July 2018) - Mrkobrada, Marko; Chan, Matthew T V; Cowan, David; Spence, Jessica; Campbell, Douglas; Wang, Chew Yin; Torres, David; Malaga, German; Sanders, Robert D; Brown, Carl; Sigamani, Alben; Szczeklik, Wojciech; et al.
Abstract : Objectives: Covert stroke after non-cardiac surgery may have substantial impact on duration and quality of life. In non-surgical patients, covert stroke is more common than overt stroke and is associated with an increased risk of cognitive decline and dementia. Little is known about covert stroke after non-cardiac surgery. NeuroVISION is a multicentre, international, prospective cohort study that will characterise the association between perioperative acute covert stroke and postoperative cognitive function. Setting and participants: We are recruiting study participants from 12 tertiary care hospitals in 10 countries on 5 continents. Participants: We are enrolling patients ≥65 years of age, requiring hospital admission after non-cardiac surgery, who have an anticipated length of hospital stay of at least 2 days after elective non-cardiac surgery that occurs under general or neuraxial anaesthesia. Primary and secondary outcome measures: Patients are recruited before elective non-cardiac surgery, and their cognitive function is measured using the Montreal Cognitive Assessment (MoCA) instrument. After surgery, a brain MRI study is performed between postoperative days 2 and 9 to determine the presence of acute brain infarction. One year after surgery, the MoCA is used to assess postoperative cognitive function. Physicians and patients are blinded to the MRI study results until after the last patient follow-up visit to reduce outcome ascertainment bias. We will undertake a multivariable logistic regression analysis in which the dependent variable is the change in cognitive function 1 year after surgery, and the independent variables are acute perioperative covert stroke as well as other clinical variables that are associated with cognitive dysfunction. Conclusions: The NeuroVISION study will characterise the epidemiology of covert stroke and its clinical consequences. This will be the largest and the most comprehensive study of perioperative stroke after non-cardiac surgery. Trial registration number: NCT01980511; Pre-results.